Inokulasi Cendawan Mikoriza Arbuskula dan Pemberian Fraksi Humat Jerami Padi pada Tanaman Jagung (Zea mays L.) di Ultisol - Ida Hodiyah (Jurnal Agrista, 2007)
The Inoculation of Arbuscular Mycorrhizal Fungi and Rice Straw Humic Substance Treatment in Maize (Zea mays L.) on UltisolABSTRACT. The pot experiment were carried out to study effect of Arbuscular Mycorrhizal Fungi (AMF) inoculation and rice straw humic substance treatment on yield of maize on ultisol. The experiment was conducted to obtain optimum rate of AMF and rice straw humic substance, which will be used as a guide to determine various rate of treatment in field experiment. The experiment used randomized block design and treatments were replicated four times. The first factor were AMF: 0, 1, 2, and 3 ton ha-1 and the second factor were rice straw humic substance: 0, 0.25, 0.5 and 0.75 ton ha-1. Result showed that the highest yield of dried maize grain were 5.2 ton ha-1 at the AMF optimum dosage of 2.4 ton ha-1 and rice straw humic substance of 0.9 ton ha-1.